C–H Bond Functionalization Using Pd- and Au-Supported Catalysts with Mechanistic Insights of the Active Species - Ishida, Tamao; Zhang, Zhenzhong; Murayama, Haruno; Yamamoto, Eiji; Tokunaga, Makoto (Synthesis, 2021)
The process of C–H functionalization has been extensively studied as a direct C–C bond-forming reaction with high atomic efficiency. Efforts have also been made on such reactions by using supported catalysts, which are superior in terms of catalyst separation from the reaction mixture and reusability. In this review, an overview of C–H functionalization reactions, especially those involving Pd- and Au-supported catalysts, is presented. In particular, we discuss reaction mechanisms, active species, leaching, reusability, etc.1 Introduction2 Types of Supported Metal Catalysts and Their Active Species3 Modes of C–H Bond Activation4 Oxidative C–H C–H Coupling of Aryl Compounds5 C–H C–H Coupling Where One Side Is Aromatic6 C–H Acylation of Aromatic Compounds and Related Reactions7 Conclusion
Keywords: C–H functionalization; Pd catalysts; Au catalysts; supported nanoparticles; immobilized complexes